Agroforestry sebagai Strategi Integratif dalam Mendukung Pembangunan Hutan Berkelanjutan: Suatu Tinjauan Pustaka - Beni Ahmadi; Wahyu Astiko (Mataram University, 2026)
Sustainable forest development faces challenges related to ecosystem degradation and the socio-economic pressures experienced by communities living around forest areas, thereby requiring an integrative management approach. Agroforestry represents a land-use system that combines trees with agricultural components and has the potential to support the balance of ecological, economic, and social functions. This article aims to analyze the role of Agroforestry in restoring forest ecological functions, examine the social, economic, and cultural factors influencing its implementation, and formulate strategies for optimizing Agroforestry practices. The study was conducted using a literature review method with qualitative content analysis of relevant national and international scientific publications. The findings indicate that Agroforestry contributes to the restoration of forest ecological functions through improving soil quality, strengthening hydrological functions, and enhancing carbon sequestration, while simultaneously reinforcing community livelihoods through income diversification. The optimization of Agroforestry through supportive policies, community capacity building, and adaptive management is essential to strengthening long-term sustainable forest development.